2019
DOI: 10.31289/agr.v1i2.2874
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Disiplin Kerja Terhadap Produktivitas Kerja Karyawan Pt Perkebunan Nusantara Iv (Persero) Unit Usaha Pabatu

Abstract: <p>This study was conducted to determine the effect of  work discipline on employee productivity at PT. Perkebunan Nusantara IV (Persero) Pabatu Business Unit. The population in this study were all employees of the department, engineering / processing,  and  general  at  PT. Perkebunan Nusantara IV (Persero) Unit Business Unit is 1031 people. the number of respondents used in this study were 104 people. The research was obtained from the results of the t test on the variables obeying all company regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
1
0
0
Order By: Relevance
“…The higher the level of work discipline among employees, the higher the level of employee work productivity (Segoro & Pratiwi, 2021). This is in line with research conducted by Andini et al (2019), Winarsih et al (2020), andSegoro &Pratiwi (2021), which explain that work discipline significantly influences employee productivity. This contrasts with the findings of the study by Saleh & Utomo (2018), which states that the work discipline variable does not affect work productivity.…”
Section: Introductionsupporting
confidence: 91%
“…The higher the level of work discipline among employees, the higher the level of employee work productivity (Segoro & Pratiwi, 2021). This is in line with research conducted by Andini et al (2019), Winarsih et al (2020), andSegoro &Pratiwi (2021), which explain that work discipline significantly influences employee productivity. This contrasts with the findings of the study by Saleh & Utomo (2018), which states that the work discipline variable does not affect work productivity.…”
Section: Introductionsupporting
confidence: 91%
“…Fitrianingrum (2015) in his research revealed that supervision has a significant effect on work discipline. The same thing was also expressed by Siregar et al, (2018) that supervision has a good impact on work discipline, and supervision has a significant effect on work discipline as revealed by Sarman et al (2015).…”
Section: Supervision Has a Positive And Significant Influence On Work...mentioning
confidence: 72%
“…Meanwhile Fadillah et al ( 2018), showed that there was no positive and significant effect between work discipline and increased work productivity. Meanwhile, Siregar (2018) in his research proved that work discipline partially does not affect work productivity. Based on the data, pre-survey results and research gaps, there are several interesting problems to study.…”
Section: Introductionmentioning
confidence: 99%
“…Disiplin kerja merupakan sikap menghormati, menghargai, patuh, dan taat terhadap peraturan yang berlaku di perusahaan, baik yang tertulis maupun tidak tertulis serta mampu menjalankannya dan tidak menghindar dari sanksi-sanksinya jika seorang karyawan melanggar tugas dan wewenang yang diberikan kepadanya oleh seorang pimpinan (Saleh & Utomo, 2018). Kedisiplinan adalah salah satu fungsi operatif dari pimpinan karena semakin disiplin karyawan, hal tersebut akan menciptakan karyawan yang berkualitas (Andini et al, 2019). Dengan adanya disiplin kerja, karyawan dapat mencapai kinerja karyawan yang maksimal.…”
Section: Latar Belakangunclassified
“…Dalam upaya meningkatkan kedisiplinan agar karyawan mematuhi semua peraturan perusahaan pemberian sanksi dilakukan secara adil dan tegas terhadap semua karyawan. Dengan keadilan dan ketegasan, sasaran pemberian sanksi tercapai (Andini et al, 2019).…”
Section: B Disiplin Kerjaunclassified